Dynamic flow stress behavior of a 5 vol.% Mg-PSZ reinforced TRIP matrix composite at ambient temperature and − 40 °C. (15th January 2017) - Decker, Sabine; Krüger, Lutz
Abstract: A composite consisting of a TRIP (Transformation Induced Plasticity) steel matrix with 5 vol.% Mg-PSZ particles (MgO partially stabilized zirconia) as reinforcement and processed by Spark Plasma Sintering (SPS) was tested under compressive load at a strain rate of 200 s − 1 at both − 40 °C and room temperature. Due to the Mg-PSZ reinforcement, the very fine-grained steel and the low temperature, the material exhibited high strength (true compressive strength of 740 MPa at 1% nominal engineering compressive strain and of 2330 MPa at 40% nominal engineering compressive strain). Adiabatic heating counteracted the phase transformation to α′-martensite. Furthermore, α′-martensite was formed in the steel phase at − 40 °C in proportions of up to 28 vol.%. The stress-induced phase transformation of the Mg-PSZ was triggered by the formation of α′-martensite. Due to the particle reinforcement, the specific energy absorption remained almost constant at both testing temperatures. Graphical abstract: Highlights: A TRIP-steel matrix composite with 5 vol.% Mg-PSZ particles was tested under compressive load at 0.001 s − 1 and 200 s − 1 . Test temperatures of − 40 °C and room temperature were used. Despite adiabatic heating at 200 s − 1 up to 28% α′-martensite were formed at − 40 °C. Due to the particle reinforcement, the specific energy absorption was kept almost constant at both testing temperatures.